Integration of Nitrifying, Photosynthetic and Animal Compartments at the MELiSSA Pilot Plant - Garcia-Gragera, David; Arnau, Carolina; Peiro, Enrique; Dussap, Claude-Gilles; Poughon, Laurent; Gerbi, Olivier; Lamaze, Brigitte; Lasseur, Christophe; Godia, Francesc (Frontiers in Astronomy and Space Sciences, 2021)
MELiSSA (Micro Ecological Life Support System Alternative) is developing bioregenerative Life Support technologies for long-term Space missions. The MELiSSA loop is conceived as a loop with several compartments, each one performing a specific function, providing all together edible material production, atmosphere regeneration, water recovery and wastes treatment. Each one of the compartments is colonized with specific bacteria or higher plants depending on its specific function. The MELiSSA Pilot Plant is a facility designed for the terrestrial demonstration of this concept, hosting laboratory rats as a crew mock-up mimicking the respiration of humans. Currently, the MELiSSA Pilot Plant focus on the integration of three compartments: Compartment 3 (nitrifying packed-bed bioreactor based on the co-culture of immobilized Nitrosomonas europaea and Nitrobacter winogradsky), compartment 4a (an air-lift photobioreactor for the culture of the edible cyanobacteria Limnospira indica with concomitant oxygen production) and Compartment 5 (an animal isolator with rats as mock-up crew). The output from these tests shows a high robustness and reliability and the performance of oxygen producing and oxygen consuming compartments is successfully demonstrated under transitory and steady-state conditions. This contribution reports on the current state of development of the MELiSSA Pilot Plant Facility and the most recent results of the integration work.